Functional Status Is Associated With 30-Day Potentially Preventable Readmissions Following Home Health Care. Issue 2 (February 2019) - Middleton, Addie; Downer, Brian; Haas, Allen; Knox, Sara; Ottenbacher, Kenneth J.
Abstract : Background: Beginning in 2019, home health agencies' rates of potentially preventable hospital readmissions over the 30 days following discharge will be publicly reported. Objectives: Our primary objective was to determine the association between patients' functional status at discharge from home health care and 30-day potentially preventable readmissions. A secondary objective was to identify the most common conditions resulting in potentially preventable readmissions. Design: This was a retrospective cohort study. Participants: A total of 1, 510, 297 Medicare fee-for-service beneficiaries discharged from home health care in 2013–2015. Average age was 75.9 (SD, 10.9) years, 60.0% were female, and 84.2% non-Hispanic white. Measurements: Thirty-day potentially preventable readmissions following home health discharge. Functional status measures included mobility, self-care, and impaired cognition. Results: The overall rate of 30-day potentially preventable readmissions was 2.6% (N=39, 452), which accounted for 40% of all 30-day readmissions. After adjusting for sociodemographic and clinical characteristics, the odds ratios for the most dependent score quartile versus the most independent was 1.58 [95% confidence interval (CI), 1.53–1.63] for mobility and 1.65 (95% CI, 1.59–1.69) for self-care. The odds ratios for impaired versus intact cognition was 1.21 (95% CI, 1.18–1.24). The 5 most common conditions resulting in a potentially preventable readmission were congestive heart failure (23.6%), septicemia (16.7%), bacterial pneumonia (9.8%), chronic obstructive pulmonary disease (9.4%), and renal failure (7.5%). Conclusions: Functional limitations at discharge from home health are associated with increased risk for potentially preventable readmissions. Future research is needed to determine whether improving functional independence decreases the risk for potentially preventable readmissions following home health care. Abstract : Supplemental Digital Content is available in the text.